Stabilization of H and D atoms in krypton-helium nanocondensates - Boltnev, R.E.; Khmelenko, V.V.; Lee, D.M. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2010)
Impurity–helium condensates formed by krypton nanoclusters containing atoms and molecules of hydrogen isotopes have been studied via an electron spin resonance (ESR) technique. Analysis of the ESR spectra has shown that most of the H and D atoms reside on the surfaces of Kr nanoclusters. Very large average concentrations have been obtained for H atoms (1.2·1019 cm−3) and D atoms (3.3·1019 cm−3) in these experiments. For the highest concentration of D atoms stabilized in the Kr–He sample, line narrowing has been observed. Exchange tunneling reactions have been studied in Kr–He sample containing H and D atoms.